Analysis Of The Role Of Self-Efficacy And Attitude In Preventing Early Pregnancy In Adolescents Through Reproductive Health Education - Zumrotul Ula; Mildaratu Mildaratu; Hartati Hartati; Rezqiqah Aulia Rahmat; Cakrawati R Cakrawati R (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
ABSTRACT Early pregnancy in adolescents is a health problem influenced by various psychological factors, including self-efficacy and attitude. Self-efficacy plays a role in shaping an individual's belief in their ability to avoid risky behavior, while attitude reflects behavioral tendencies towards reproductive health. This study aims to analyze the role of self-efficacy and attitude in preventing early pregnancy in adolescents through reproductive health education. This study used a quantitative design with a cross-sectional approach . A sample of 110 respondents was selected using a purposive sampling technique. Data were collected using a questionnaire and analyzed using multiple linear regression. The results showed that self-efficacy (β = 0.45; p < 0.001) and attitude (β = 0.32; p < 0.01) significantly influenced early pregnancy prevention behavior, with self-efficacy as the most dominant factor. Reproductive health education has been shown to improve both variables. In conclusion, increasing self-efficacy and positive attitudes through education is an important strategy in preventing early pregnancy in adolescents. Keywords: Self-Efficacy , Attitude, Adolescents, Early Pregnancy, Reproductive Education